Curtailed electricity and hydrogen in Association of Southeast Asian Nations and East Asia Summit: Perspectives form an economic and environmental analysis. (8th July 2022) - Chang, Youngho; Phoumin, Han
Abstract: This study examines how well producing hydrogen via electrolysis from curtailed electricity from renewables could fulfil environmental benefits against the cost of producing hydrogen via electrolysis in the context of the Association of Southeast Asian Nations (ASEAN) and the East Asia Summit (EAS). The cost of producing hydrogen via electrolysis ranges from less than USD 2 per kgH2 when the electrolyser load factor is 1500 h or above to USD10 per kgH2 or even higher when the electrolyser load factor is 500 h or lower. The amount of CO2 emissions abated by hydrogen produced from curtailed electricity from renewables ranges from about 130 million tonnes to about 150 million tonnes for ASEAN and from about 18, 000 million tonnes to about 19, 000 million tonnes for EAS. Applying prevailing carbon prices to the CO2 emissions abated, the possible monetised benefits of hydrogen produced via electrolysis from curtailed electricity from renewables range from about USD0.25 per kgH2 to about USD9.00 per kg H2 for ASEAN and from about USD0.50 per kgH2 to about USD15.00 per kg H2 for EAS. The results of the cost-benefit analysis suggest that the price of carbon needs to be about USD15 per tonne of CO2 to justify hydrogen produced via electrolysis from curtailed electricity from renewables for both ASEAN and EAS. The results also suggest that high electrolyser load factors make hydrogen produced via electrolysis from curtailed electricity from renewables cost-competitive even under low carbon prices. Highlights: A cost-benefit analysis is performed for producing hydrogen from curtailed electricity. Hydrogen from curtailed electricity appears not to be cost-effective with current carbon prices. Carbon price about 15 per tonne of CO2 justifies hydrogen from renewables for both ASEAN and EAS. High electrolyser load factors make hydrogen from renewables cost-competitive. Low electrolyser load factors require significantly high carbon prices.